Sclerosing Mesenteritis as a Cause of Abdominal Mass and Discomfort in an Elderly Patient: A Case Report and Literature Review. (14th June 2010) - Ali, Farzana Nawaz; Ishaque, Sidra; Jamil, Bushra; Nasir-Ud-Din,; Idris, Muhammad
Abstract : Sclerosing mesenteritis is a rare benign process that involves inflammation, fat necrosis, and fibrosis of the mesentery. The disease poses great diagnostic challenge due to its nonspecific clinical and diagnostic findings. We report the case of a 75-year-old man who presented with vague abdominal discomfort associated with an intra-abdominal mass. With suspicion of a bowel carcinoid tumor on computed tomography scans, the patient underwent diagnostic laparoscopy. A diagnosis of sclerosing mesenteritis was made on histological examination. The patient's symptoms responded to a combination of immunosuppressive drugs, with no interval change in the size of the mass on radiological examination after fifteen months.